Occupancy, colonization and extinction patterns of rabbit populations: implications for Iberian lynx conservation - Sarmento, Pedro (2019)
In Mediterranean ecosystems, rabbits are a key prey species for many predators, such as the Iberian lynx, which is threatened with extinction and has gone extinct locally in several regions of its historical distribution range. One of these regions is Serra da Malcata Nature Reserve, Portugal, which is also currently proposed as a potential site for reintroduction. We intended to investigate annual variation, potential time trends and the effects of management practices on the rabbit population in Serra da Malcata as a model for future potential reintroduction areas. The rabbit population was monitored over 12 years (from 1997 to 2009) by counting latrines along linear transects. These data were used to estimate rabbit occupancy, colonization and extinction patterns using a likelihood-basedmethodincluding habitat, population and topographic covariate effects. Our results suggest that initial occupancy, when management practices were absent, was driven by the presence of Erica spp. and Cistus ladanifer shrubs and by distance to summits. Site colonization was positively influenced by the presence of edges between shrubs and pastureland and by patterns of rabbit distribution in the previous sampling season. On the other hand, local extinction was negatively influenced by edges. We conclude that the increase in rabbit occupancy and local colonization patterns was clearly associated with management actions (particularly, the creation of pasturelands), although the recovery of the species was noticeably limited by previous patterns of spatial distribution.